(untitled) (Desenvolvimento em Questão, 2025)
The objective of this study was to analyze the correlation between socioeconomic development and the incidence of violent crime, specifically in the sugarcane-producing municipalities of São Paulo, Goiás and Minas Gerais (the three main producing states in Brazil). To this end, Spearman’s correlation coefficient was used, a non-parametric measure that best suits the purposes of this analysis. Socioeconomic development was measured by the Firjan Municipal Development Index (IFDM) and violent crime was measured by the homicide proxy. The results showed a non-significant coefficient for the three states and it was not possible to reject the null hypothesis at acceptable significance levels.